Experimental investigation of the effects of coolant temperature in a turbocharged stratified injection (TSI) engine fuelled with gasoline and liquefied petroleum gas - Özer, Salih; Demir, Usame; Coskun, Gokhan (Elsevier Sci Ltd, 2023)
This study investigates the effects of using the TSI engine with alternative fuels, which many commercial vehicle brands have started to prefer in their vehicles. This study investigated turbocharged stratified injection engine (TSI) emissions using different coolant temperatures (20 degrees C, 40 degrees C and 90 degrees C) under steady-state operating conditions. Three different fuel strategies were used: gasoline, gasoline with liquefied petroleum gas (LPG), and liquid LPG. Furthermore, three different operating conditions as motoring, 2500 RPM-105 km/h and 3500 RPM145 km/h were applied in experimental studies. The results indicated that cooling temperature has a strong effect on emissions that in cold working conditions due to incomplete combustion, NOx emissions were decreased while CO and HC emissions were increased. From the results, emissions of liquid DI-TSI LPG fuel were more sensitive than other fuels to coolant temperature, and increasing the temperature decreases the HC and CO emissions more than other fuels.
Keywords: Tsi Engine; Coolant Temperature; Gasoline Direct Injection; Lpg Indirect Injection; Lpg Direct Injection; Particulate Matter; Combustion; Emissions; Gdi; Ethanol